THU0339 PULMONARY INVOLVEMENT AND OUTCOME IN SYSTEMIC SCLEROSIS (SSC) – ILD-PH AS AN IMPORTANT SUBSET. (June 2019) - Kreuter, Michael; Bonella, Francesco; Müller-Ladner, Ulf; Siegert, Elise; Henes, Jörg; Riemekasten, Gabriela; Blank, Norbert; Schmalzing, Marc; Koetter, Ina; Guenther, Claudia; Schmeiser, Tim; Zeidler, Gabriele; et al.
Abstract : Background: Pulmonary involvement is the leading cause of death in SSc and can manifest as interstitial lung disease (ILD), pulmonary hypertension (PAH) or a combination (ILD-PH). Aim of this analysis was to determine prevalence, clinical characteristics and outcomes of different forms within the German SSc Network. Objectives: Methods: SSc patients were analyzed for pulmonary involvement, clinical characteristics and outcome. Results: There were 3699 pts in 42 centers with a mean follow up time of 34.4±12.6 months. At baseline, ILD was frequent (29.5%), while ILD-PH and PAH had lower prevalences (7.5%, 6.1%). At the end of follow up, 32% of SSc pts had ILD, 13% ILD-PH and 7% PAH. ILD and ILD-PH were more frequent in the diffuse form (47%, 12%), while PAH did not differ between subforms. Significant differences in baseline characteristics between PAH vs. ILD-PH vs. ILD were found for age (62, 59, 54 years), sex (males: 15%, 22%, 24%) and smoking prevalence (non-smokers 49%, 63%, 57%). Mean DLCO and FVC were 56%/93% for PAH, 49%/78% for ILD-PH and 56%/81% for ILD. Significant decreases for DLCO (≥15%) and FVC (≥10%) were found in 45%/26% in PAH, 45%/26% for ILD-PH and 36%/16% in ILD. All-cause mortality was 8.1% for the total cohort and differed significantly between patients without pulmonary involvement (4%), ILD (7.8%), PAH (14.2%), and ILD-PH (21%, p<0.001). Conclusion: ILD is the most prevalent pulmonary involvement in SSc, while PH-ILD is associated with the most detrimental survival. Significant differences in baseline characteristics of types of pulmonary SSc involvement may help to identify patients at risk in the future. Disclosure of Interests: : Michael Kreuter Grant/research support from: Boehringer Ingelheim, Roche Pharma, Consultant for: Boehringer Ingelheim, Roche Pharma, Speakers bureau: Boehringer Ingelheim, Roche Pharma, Francesco Bonella Consultant for: Boehringer Ingelheim, Roche Pharma, Speakers bureau: Boehringer Ingelheim, Roche Pharma, Ulf Müller-Ladner Grant/research support from: Projekt supported by an unrestricted educational grant from Celgene GmbH., Elise Siegert Shareholder of: Astra Zeneca, Grant/research support from: Actelion, Consultant for: AEC Partners, Speakers bureau: Actelion, Norsk, Jörg Henes: None declared, Gabriela Riemekasten Consultant for: Chugai, F. Hoffmann-La Roche, Speakers bureau: Chugai, F. Hoffmann-La Roche, Norbert Blank Grant/research support from: SOBI and Novartis, Speakers bureau: Novartis and SOBI, Marc Schmalzing Grant/research support from: Pfizer, Chugai, MSD, Janssen-Cilag, BMS, Celgene, UCB, Consultant for: Abbvie, Chugai, Genzyme, Hexal/Sandoz, MSD, Novartis, Roche, Sanofi Pasteur, Speakers bureau: Actelion, Baxalta/Shire, BMS, Celgene, Chugai, Janssen-Cilag, MSD, Novartis, Pfizer, Roche, UCB, Ina Koetter: None declared, Claudia Guenther Grant/research support from: Pfizer, Novartis, Employee of: 20 years ago, Novartis, Speakers bureau: Celtis, Tim Schmeiser Speakers bureau: Actelion, UCB, Pfizer, Gabriele Zeidler Grant/research support from: MSD Sharp & Dohme GmbH Actelion Pharmaceuticals Deutschland GmbH Roche Pharma AG AbbVie Deutschland GmbH Co. KG Pfizer Pharma GmbH Lilly Deutschland GmbH Celgene GmbH Bristol-Myers Squibb UCB Pharma GmbH/UCB GmbH, Speakers bureau: MSD Sharp & Dohme GmbH Actelion Pharmaceuticals Deutschland GmbH Roche Pharma AG AbbVie Deutschland GmbH Co. KG Pfizer Pharma GmbH Lilly Deutschland GmbH Celgene GmbH Bristol-Myers Squibb UCB Pharma GmbH/UCB GmbH, Alexander Kreuter Speakers bureau: Actelion Pharma, MSD, AbbVie, InfektioPharm, Margitta Worm: None declared, Laura Susok: None declared, Aaron Juche: None declared, Christiane Pfeiffer: None declared, Cord Sunderkoetter: None declared, Donja Homayoon: None declared, Kathrin Kuhr: None declared, Hanns-Martin Lorenz: None declared, Pia Moinzadeh Speakers bureau: Actelion, Nicolas Hunzelmann Speakers bureau: Boehringer Ingelheim, Actelion, Pfizer, Roche